Development characteristics of football coaches in Australia and Malaysia - Zulakbal Abd Karim (2016)
Sport coaches play a crucial role in contributing to individual and team performance. Unlike thescientific study of athlete development, scant attention has been paid to the intricacies of coachdevelopment across the full spectrum of coaching levels. In the current research the defining stagedevelopment characteristics of A, B and C license soccer (hereafter referred to as football)coaches in Australia and Malaysia, were interviewed about their development journey, especiallydating back to their first involvement in football through to thepresent.MethodsThis research was guided by evolved grounded theory (EGT), (Strauss & Corbin, 1990) principles.Evolved grounded theory was used and is well suited to developing an understanding of thecomplexities of sport coaching development (Pellegrino, Chudowsky, & Glaser, 2001). Furthermore,EGT is inherently adaptable and is data driven but with the capacity to consider relevant researchwith a view to developing an explanatory model. Coaches' learning changes as they learn fromdifferent sources that change their cognitive structure (Werthner & Trudel, 2006). Suitableaccredited football coaches were progressively recruited based on the principles of theoreticalsampling (Strauss & Corbin, 1990, 1998).InterviewsIn-depth semi-structured face-to-face interviews were used to explore how participants organizedand understood their coaching development perspectives and experiences. I used a semi-structuredinterview guide with a recursive design, whereby themes were identified and explored in laterinterviews. The transcripts from twenty-four interviews conducted over an 11-month period inAustralia andMalaysia were transcribed and analyzed according to EGT principles. Probe questions were also usedto explore idiographic themes and issues relevant to each interviewee. Initially data analysisinvolved creating verbatim transcripts of each interview resulting in 372 pages of single spacedtext. Following the principle of Strauss & Corbin's, (1990) EGT, I systematically conducted dataconstruction, data deconstruction, and data reconstruction stages.ResultsAs expected, development emerged as a central overarching category.Based on the analysis, the following four core development themes emerged, a) pre-accreditation, b)characteristics, c) learning and d) challenges. These core categories were relevant for bothAustralian and Malaysian football coach samples were underpinned by over 15 selected common codes,over 70 axial codes and close to 3,000 open codes. These four development themes formed the basisfor the resultant evolved grounded model. Although the development themes for the Australian andMalaysian coaches were very similar two sub-themes related to egalitarianism coaching attitudes inAustralia and hierarchical practices in Malaysia emerged.ConclusionThe use of EGT proved to be a useful methodology to delineate key development themes for accreditedfootball coaches across a wide spectrum of coaching contexts. The aims of the study were achievedand the accredited football coach development model (AFCDM) will hopefully provide an impetus toexamine further coach development and particularly strategies and techniques to ensure all coachesare well supported, trained and developed.